Centro de desarrollo juvenil, barrio Santa Clara, escala barrial - Fuertes Ortega, Valeria Alexandra (2020)
The workshop AR0 960 2019-1 develops the Urban Plan for neighborhoods Larrea and Santa Clara, that are located in an urban zone with high historical content within the city; it currently has a high rate of urban problems, mainly the decrease of population, with a high rate of displacement to the outskirts by young and adolescent users, specially women, causing the urban decay of the place. This is due to insecurity and low quality in public spaces; therefore, in spite of being a neighborhood surrounded by services, there are no youth recreational equipment that cover the necessity of the same. The urban plan proposes to include equipment of various uses and scales, adapted to the needs of the youth and teens; within the recreational educative axis. One of them is called, Center of Youth Development, Neighborhood Santa Clara, Neighborhood Scale, that is located on street San Gregorio, between streets Antonio de Ulloa and Versalles, behind the Administrative Faculty of Sciences in UCE, the goal of this equipment is to satisfy the needs of the users between 10-24 years of age, specially the students of the university. Through revitalizing the public space, acquiring places or recreation and education, designed to be used during their free time, that is essential for the correct development of novices.